Chemical Composition of Essential Oil of Local Endemic Salvia kronenburgii Rech. fil. to Turkey - Kocak, A.; Bagci, E. (Taylor & Francis Ltd, 2011)
In this study, essential oil composition of local endemic Salvia kronenburgii Rech. fil. to Turkey were determined. The aerial parts of Salvia kronenburgii Rech. fil were hydro-distilled to produce the oil in the yields of 0.7 v/w. The chemical composition of the essential oil of dried aerial parts of S. kronenburgii was analyzed by GC and GC-MS. Fifty four components were identified representing 87.08% of the oil. Limonene (11.77%), 2-cyclohexen-1-ol (9.25%), trans-verbenol (7.70%) and trans-(+)-carveol (6.77%) were found to be major components in S. kronenburgii. The distribution of the essential oil constituents was discussed in Salvia genus patterns.
Keywords: Salvia kronenburgii; Lamiaceae; GC-MS; Essential oil; Limonene; chemotaxonomy